Work Stressors Before and During COVID-19 Pandemic and Factors Related to Workers in the Heavy Equipment Manufacturing Industry of PT.X - Yunianti Lafau; Nuri Purwito Adi; Amilya Agustina; Muhammad Ilyas; Agus Sugiharto (eJournal Kedokteran Indonesia, 2023)
Psychosocial hazards are a major public health problem, so it is necessary to prevent and manage them so as not to cause mental and physical harm to workers. This study aims to determine changes in work stressors before and during the COVID-19 pandemic and related factors to workers in the PT.X Heavy equipment manufacturing industry. The study used a retrospective cohort design from 2018 and 2021 Medical Check-Up (MCU) data with a Stress Diagnosis Survey (SDS) questionnaire. Research was conducted from October 2021 until July 2022 with samples of 146 obtained. Bivariate analysis using proportion and mean test. The research found that the increase in moderate-severe stressors before and during the pandemic was role ambiguity, role conflict, quantitative workload, and career development. On the other hand, qualitative workloads and responsibility for others decreased during the pandemic. The most worsened was role ambiguity and responsibility for others. Based on the type of production and non-production work, there was a significant relationship to quantitative workload before the pandemic (p=0.043), and not significant during the pandemic. Furthermore, there is a significant relationship with qualitative workload during the pandemic (p = 0.043), and it was not significant before the pandemic. It can be concluded that the Pandemic conditions caused an increase and decrease in work stressors analysed in workers in the heavy equipment manufacturing industry.